2019
DOI: 10.52547/nkums.11.1.44
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Cognitive-Behavioral Therapy based on Beck’s Pattern on Clinical Syndrome and Life Satisfaction in Patients with Major Depression

Abstract: Introduction:The aim of this study was to evaluate the effectiveness of Cognitive-behavioral therapy based on Beck's pattern on clinical syndrome and life satisfaction in patients with major depression Methods: This randomized clinical trial was performed on 24 patients with depression. Patients were randomly assigned into two groups of cognitive-behavioral therapy and control. Cognitivebehavioral therapy based on Beck's pattern was conducted in twelve nine-minute sessions twice a week, and the control group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to the study, no significant differences were observed between the control and intervention groups concerning demographic parameters, such as age, gender, marital status, place of residence, history of physical and mental illness, duration of illness, and history of medication, and thus the patients in the groups were homogeneous concerning the demographic features. The occurrence of major depressive disorder was twice as high in women compared to men almost all over the world and in all countries and cultures [ 8 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the study, no significant differences were observed between the control and intervention groups concerning demographic parameters, such as age, gender, marital status, place of residence, history of physical and mental illness, duration of illness, and history of medication, and thus the patients in the groups were homogeneous concerning the demographic features. The occurrence of major depressive disorder was twice as high in women compared to men almost all over the world and in all countries and cultures [ 8 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depression results in reduced energy, disinterest, guilt, difficulty concentrating, anorexia, death and suicide thoughts, insomnia, oversleeping, and dysfunction [ 7 ]. Additionally, depression has been linked to an increased risk of developing conditions such as diabetes, stroke, and heart disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation